Etiology of Cryptogenic Stroke - G. R. Ramazanov; T. A. Magomedov; L. T. Khamidova; N. V. Rybalko; S. S. Petrikov; N. A. Shamalov (Неотложная медицинская помощь)
Ischemic stroke is a heterogeneous syndrome with a plurality of potential etiological factors. The routine diagnosis does not always allow the cause of acute cerebrovascular accident to be found, in such cases we talk about cryptogenic ischemic stroke, which incidence is 20-40%. The category of patients with cryptogenic stroke was first characterized and assigned to a separate group in the database of the National Institute of Neurological Diseases and Stroke in the USA, and later in the TOAST study. The diagnosis of cryptogenic stroke is usually based on the exclusion of well-known causes of acute cerebrovascular accidents, such as atherosclerosis, cardiac arrhythmias, arterial hypertension. Due to the considerable variability of concepts for cryptogenic stroke, the term ESUS (Embolic Stroke of Undetermined Source) appeared in 2014 and formulated criteria which accurately characterized these patients: non-lacunar cerebral infarction by CT and/or MRI, no atherosclerotic lesion stenosing a stroke-associated artery of more than 50%, no sources of high-risk cardioembolism, no other causes of stroke such as dissection of the artery supplying the area of infarction in the brain, migraine, arteritis. Among the potential causes and sources of cerebral embolism in patients with cryptogenic stroke are heart, veins of lower extremities and pelvis, nonstenosing atherosclerosis of brachiocephalic artery, atheroma of aortic arch, paradoxical embolism non-atherosclerotic vasculopathy, monogenic diseases, hypercoagulable states, and others. We should note that there is a lot of studies on the possible causes of cryptogenic stroke in the available literature, but no common approach to classification of etiologic factors and examination algorythms were developed. The high incidence of cryptogenic stroke, the significant heterogeneity of its etiopathogenetic mechanisms and the need for differentiated approaches to the secondary prevention of this type of acute cerebrovascular accident determine the relevance of further studies in this field.